Development of “Trade War” Business Simulation Educational Game Using Unity - Mulyadi Kamsul; Aina Damayunita; Rifqi Syamsul Fuadi (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the effect of learning media business simulation educational game